PADANAN PARTIKEL AKHIR KALIMAT-YOPADANOVEL NIJI NO SHOUNENTACHI DALAM BAHASA INDONESIA - Emeli Rae Bora; Arza Aibonotika; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Japanese language has a sentence final particle used as auxiliary word that explain the sentences delivered by speaker includes the opinions, questions and feeling of the speaker to the listener.Japanese language has a variety of shuujoshi like ka, yo, ne, na, zo, ze and so on. This study examines the functions of shuujoshi yo and equivalents in Indonesian. This study aims to describe the function and know the equivalents of shuujoshi yo. This research uses Niji No Shounen Tachi as a source of data which the Niji No Shounen Tachi is a Japanese translation novel translated by Hiroaki Kato from the Indonesian language novel titled Laskar Pelangi by Andrea Hirata. For data collection using the refer method with basic tapping techniques and to explain the function and know the equivalent used translational equivalent method. Based on the results of theanalysis it was found that the function of the shuujoshi yo to deny dissent’s different opinion from oneself, reminding something that the listener forgot and convey something that the listener does not know and realize. From the three functions, it can be concluded that the appearance of shuujoshi yo is based on the assumption that there is a mismatch of information and knowledge between the speaker and the listener. Shuujoshi yo which is used in sentence demands such as commands, prohibitions, requests and socialization are based on the conflict assumption between the speaker and the listener. Shuujoshi yo that appears in Japanese novels is partially paires with the form –lah, -kah, and the most do not have and equivalents in form or word.KeyWords: Shuujoshi, Yo, Equivalent, Function